How to test the on-ice aerobic capacity of speed skaters? An on-ice incremental skating test for young skaters - Kong, Z.; Zhang, H.; Zhang, M.; Jia, X.; Yu, J.; Feng, J.; Zhang, S. (International Journal of Environmental Research and Public Health, 2023)
Aerobic capacity is important for speed skaters to achieve good results in middle-long distance events. The technical characteristics of speed skating cause intermittent blood flow blockage in the lower limbs. Therefore, an athlete`s aerobic capacity on ice may differ from that measured by cycling or running. Now, the on-ice aerobic capacity lacks methods for conducting aerobic capacity tests on ice.